Analysis of Amino Acid Changes in the Fusion Protein of Virulent Newcastle Disease Virus from Vaccinated Poultry in Nigerian Isolates - Funsho-Sanni, Olubukola O.; Ella, Elijah E.; Rogo, Lawal D.; Sanni, Olufunsho S.; Inabo, Helen I.; Luka, Sodangi A.; Shittu, Ismaila (International Journal of Microbiology, 2022)
The roles of fusion gene in the virulence of Newcastle disease virus are well established, but the extent of its variation among the XIV, XVII, and XVIII genotypes reported in Central Africa and West Africa has until recently been understudied. In this study, virulent Newcastle disease virus (vNDV) was isolated from dead chickens among vaccinated flocks between March and April 2020. Fusion (F) gene was sequenced and analysed for characterization and information about genetic changes. Many substitutions were observed along the region and some of their functions are yet to be determined. Results showed that all study isolates have virulent cleavage site sequence 112-RRRKR-116/F117 and clustered within genotype XIVb. Sequence analysis showed K78R mutation in the A2 antigenic epitope in all isolates and more along the F-gene which varied in some instances within the isolates. Mutation in this A2 antigenic epitope has been reported to induce escape mutation to monoclonal antibodies generated using the NDV LaSota strain. The range of percentage nucleotide and amino acid homology between the study isolates and commercially available vaccine strains is 81.14%–84.39% and 0.175–0.211, respectively. This report provides evidence of vNDV among vaccinated chicken flock and molecular information about circulating vNDV strains in Kano State, Nigeria, which is useful for the development of virus matched vaccines. Newcastle disease (ND) surveillance and molecular analysis of circulating strains in this region should be encouraged and reported. Furthermore, ND outbreaks or cases among vaccinated poultry presented to veterinary clinics should be reported to the state epidemiologist. Nucleotide sequences were assigned accession numbers OK491971–OK491977.